On Fuzzy Solutions for Diffusion Equation - Jefferson Leite; Moiseis Cecconello; Jackellyne Leite; R. C. Bassanezi (Journal of Applied Mathematics)
Our main goal is to define a fuzzy solution for problems involving diffusion. To this end, the solution of fuzzy diffusion-reaction-advection equation will be defined as Zadeh’s extension of deterministic solution of the associated problem. Important aspects such as unity and stability of these solutions will also be studied. Graphical representations of these solutions will be presented.